Eating pattern, nutrient utilization and rumen metabolites in goats fed Dichanthium annulatum-browse leaves diets - SINGH, SULTAN; KUNDU, S S (The Indian Journal of Animal Sciences, 2013)
The present study was conducted to assess the supplementary effect of tropical browse species leaves on feed intake,nutrients utilization, rumen metabolites and water kinetics of goats fed Dichanthium annulatum grass based diets. In an experiment 4 adult male local goats, weighing 30.0Â±2.1 kg, were fed Dichanthium annulatum-Hardwickia binata (DAHB), Dichanthium annulatum-Securegeia virosa (DA-SV), Dichanthium annulatum-Leucaena leucocephala (DA-LL) and Dichanthium annulatum-Helectris isora (DA-HI) grass: tree leaves diets in 50: 50 ratios in 4 separate feeding trials.A digestion-cum-metabolism trial was conducted to determine intake, nutrients utilization and nitrogen (N) balance.Rumen liquor was collected at 0 and 4 h feeding after 60 and 90 days of feeding to estimate rumen metabolites, whilefor water kinetics rumen liquor was drawn once at 90 days of feeding from an individual goat in each trial. DMI of goats was highest on DA-HI and lowest on DA-HB diet. Goats exhibited higher digestibility of CP, NDF, ADF and celluloseon DA-HI than other diets. Faecal N loss was higher from DA-LL, while urinary N loss was more from DA-HI and DALL.N balance (g/d) was highest in DA-LL and lowest in DA-HB. Goats had higher eating rate at first and fourth hourof feeding on tested diets, while meal consumption was highest on DA-LL and lowest on DA-HB diet. Goat rumenliquor had higher TVFA and N metabolites on DA-LL. Goats exhibited higher dilution rate and out flow rate on DA-HIand DA-LL diets than DA-SV and DA-HB diets. Results revealed that goats had higher DMI and nutrients digestibilityon DA-HI and DA-SV diets, while N balance and rumen metabolites production was more on DA-LL diets.